Fuzzy Synchronization Control for Fractional-Order Chaotic Systems With Different Structures - Xu, Jin; Li, Ning; Zhang, Xiulan; Qin, Xiaoli (Frontiers in Physics, 2020)
This paper discusses the synchronization problem for a class of unknown fractional-order chaotic systems (FOCSs) with indeterminate external disturbances and non-symmetrical control gain. A paralleled adaptive fuzzy synchronization controller is constructed, where indeterminate non-linear functions are approximated by the fuzzy logic system depended on fractional-order Lyapunov stability criteria, and the fractional-order parameter adaptive law is designed to regulate corresponding parameters of the fuzzy systems. The proposed method guarantees the boundedness of all the signals in the closed loop system, and at the same time, it ensures the convergence of the synchronization error between the master and slave FOCSs. Finally, the feasibility is demonstrated by simulation studies.